Anticoagulation control for nonvalvular atrial fibrillation in a tertiary academic centre in Johannesburg - Vanessa Mogashoa; Dineo Mpanya; Nqoba Tsabedze (Thrombosis Journal)
Abstract Background Atrial fibrillation is a growing epidemic in Africa. Anticoagulation, considered the backbone for non-valvular atrial fibrillation (NVAF) management, is limited to warfarin as the mainstay of available anticoagulation therapy in most low- and middle-income countries (LMIC). The optimal time in the therapeutic range (TTR) while on warfarin is essential to avoid bleeding and thromboembolic complications. This study assessed anticoagulation control in patients with NVAF on warfarin in Johannesburg, South Africa. Methods We conducted a cross-sectional retrospective study on patients with NVAF managed in the Division of Cardiology, at a tertiary-level academic centre in Johannesburg, South Africa, between 1 January 2015 and 31 December 2019. Anticoagulation control for patients with NVAF was assessed by calculating the TTR using the Rosendaal method. Results The study population comprised 177 patients diagnosed with NVAF. The mean age was 65.0 ± 13.1 years. The median TTR among patients with NVAF was 46% [interquartile range (IQR): 8.7–86.0], and 63 (35.6%) patients with NVAF had a TTR ≥ 70% (optimal anticoagulation control). Patients with poor anticoagulation control (TTR < 70%) were on warfarin for a shorter duration compared with those with optimal anticoagulation control [56 days (IQR: 43–84) vs. 70 days (IQR: 56–140), p = 0.0013]. The mean CHA2DS2-VASc score was 4 ± 1.5, and it did not differ between patients with poor or optimal anticoagulation control. Among the 175 patients with available HAS-BLED scores, 21 (12.0%), 112 (64.0%) and 42 (24.0%) were at a low, moderate, and high risk for bleeding, respectively. Of the 21 patients in the HAS BLED low-risk category, only 4 (19.0%) had a TTR < 70% (p < 0.001). Warfarin toxicity was documented in 13 (7.3%) patients. Conclusion In our study, a TTR ≥ 70%, suggesting optimal anticoagulation control, was found in only 35.6% of patients with NVAF on warfarin.